Chronic low-frequency electromagnetic field exposure before and after neonatal life induces changes on blood oxidative parameters of rat offspring - Guleken, Zozan (Annals of Medical Research, 2021)
Aim: It is aimed to investigate the chronic effects of extremely low-frequency magnetic fields (ELF-MF) exposure on blood oxidative and anti-oxidative levels. Rat offsprings during intrauterine (IU) and extrauterine (EU) period exposure to chronic 50 Hz electromagnetic fields included to the study to see the ELF-MF induced changes in blood biochemical levels. To evaluate the cell’s physiological response, the levels of glutathione (GSH) and malondialdehyde (MDA) were measured as a label. Recently, the use of electromagnetic (EM) energy has increased in worldwide. Numerous reports indicate that prenatal and postnatal period repetitive ELF-MF leads to health-related issues on physiological responses and affect the activity of the enzymes.Materials and Methods: Pregnant female Wistar Albino rats (n = 21), weighing 250 – 300 g were randomly divided into MF exposed group (Group I) and sham group (Group II). Eleven pregnant females were exposed to MF for 24 hours a day for IU exposure and exposed to 50 Hz 500μT ELF-MF radiating magnetic field cages for 24 hours for the duration of pregnancy for 21 days. Following the birth, first generation newborn rats (n=11) were continued to expose 50 Hz 500μT ELF-MF, 24 hours, for additional 50 days in EU period. Sham group (n=10) without any radiation. Groups’ blood samples were collected and analyzed. The levels of an oxidative stress marker MDA and antioxidant scavenger GSH activities were investigated. Results: Long-term exposure to ELF-MF increased MDA concentration in blood plasma of rat offspring and decreased GSH levels significantly. No correlation was shown between MDA and GSH levels. Conclusion: Long-term ELF-MF exposure causes oxidative stress that results an increase on lipid peroxidation and a reduction on antioxidative parameters of blood tissue.
Keywords: Blood; ELF-MF; GSH; magnetic field; MDA; postnatal exposure; prenatal exposure